Diffusion Imaging Findings in US Service Members With Mild Traumatic Brain Injury and Posttraumatic Stress Disorder. Issue 6 (November 2018) - Bolzenius, Jacob D.; Velez, Carmen S.; Lewis, Jeffrey D.; Bigler, Erin D.; Wade, Benjamin S. C.; Cooper, Douglas B.; Kennedy, Jan E.; Reid, Matthew W.; Ritter, John L.; York, Gerald E.; Tate, David F.
Abstract : Objective: Use diffusion tensor imaging to investigate white matter microstructure attributable to mild TBI (mTBI) and/or posttraumatic stress disorder (PTSD). Participants: Twenty-seven individuals with mTBI only, 16 with PTSD only, 42 with mTBI + PTSD, and 43 service members who sustained orthopedic injury. Design: Descriptive cross-sectional study. Main Measures: Clinical diffusion tensor imaging sequence to assess fractional anisotropy, mean, axial, and radial diffusivity within selected regions of interest. Results: Corrected analyses revealed a pattern of lower white matter integrity in the PTSD group for several scalar metrics. Regions affected included primarily right hemisphere areas of the internal capsule. These differences associated with the PTSD only cohort were observed in relation to all 3 comparison groups, while the mTBI + PTSD group did not exhibit any notable pattern of white matter abnormalities. Conclusion: Results suggest that lower resolution scan sequences are sensitive to post–acute abnormalities associated with PTSD, particularly in the right hemisphere. In addition, these findings suggest that ongoing PTSD symptoms are associated with differences in white matter diffusion that are more readily detected in a clinical scan sequence than mTBI abnormalities. Future studies are needed to prospectively assess service members prior to onset of injury to verify this pattern of results. Abstract : Supplemental Digital Content is Available in the Text.